2017
DOI: 10.1186/s41038-017-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex steroid hormones on the response to trauma and burn injury

Abstract: Trauma and related sequelae result in disturbance of homeostatic mechanisms frequently leading to cellular dysfunction and ultimately organ and system failure. Regardless of the type and severity of injury, gender dimorphism in outcomes following trauma have been reported, with females having lower mortality than males, suggesting that sex steroid hormones (SSH) play an important role in the response of body systems to trauma. In addition, several clinical and experimental studies have demonstrated the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 162 publications
1
21
0
Order By: Relevance
“…In the current study, we also found that the gender difference is an independent prognostic factor of esophageal fistula. Furthermore, the impact of estrogen on regulating metabolic and organ responses following injury has been revealed by some studies [27][28][29]. Therefore, females have an advantage in injury recovery, which may lead to gender differences in the occurrence and prognosis of esophageal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we also found that the gender difference is an independent prognostic factor of esophageal fistula. Furthermore, the impact of estrogen on regulating metabolic and organ responses following injury has been revealed by some studies [27][28][29]. Therefore, females have an advantage in injury recovery, which may lead to gender differences in the occurrence and prognosis of esophageal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Being male and a victim of trauma is associated with increased mortality, length of hospital stay and secondary complications such as infections and multiple organ failure. This suggests that the female sex steroid hormones may have a protective effect in trauma [7, 25]. The apparent female advantage [26] and differences in survival with age [27] have led to the consideration of the role of the sex steroid precursor hormone DHEA, whose levels decline with age and differ between the sexes.…”
Section: Reviewmentioning
confidence: 99%
“…Additionally, those trauma victims aged over 75 years have an increased morbidity and mortality rate [6]. The differences in sex steroid hormones and their precursors between genders and across the lifespan may thus influence outcomes in the trauma patient population [7].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen improves myocardial and hepatocellular functions and decreases lung congestion after trauma. In contrast, endogenous testosterone depresses the immune response and causes the impairment of organ functions following trauma and blood loss [ 31 ]. Some studies using human and animal models have revealed that the sex hormones play an important role in the body’s response and affect clinical outcomes [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, endogenous testosterone depresses the immune response and causes the impairment of organ functions following trauma and blood loss [ 31 ]. Some studies using human and animal models have revealed that the sex hormones play an important role in the body’s response and affect clinical outcomes [ 31 , 32 , 33 ]. The Women’s Health Initiative has validated the value of long-term hormone therapy in women at risk of osteoporosis, in which the female patients in the studied population had benefited from this policy and had a survival advantage [ 34 ].…”
Section: Discussionmentioning
confidence: 99%